Control of firing mode of corticotectal and corticopontine layer V burst-generating neurons by norepinephrine, acetylcholine, and 1S,3R- ACPD - Wang, Z (J Neurosci, 1993)
The ionic mechanisms by which the firing mode of layer V burst- generating neurons is modulated by noradrenergic, cholinergic, and glutamate metabotropic receptors were investigated with intracellular and extracellular recordings obtained in slices of guinea pig sensorimotor and primary visual cortices maintained in vitro. Extracellular and intracellular recordings revealed that a subset of layer V cells spontaneously generated bursts of three to six action potentials with an interburst frequency of 0.2–4 Hz. Depolarization of these cells with the intracellular injection of current inhibited burst firing and switched the cells to the tonic, single-spike mode of action potential generation. Intracellular recording from retrogradely labeled layer V pyramidal cells that project to either the superior colliculus or pontine nuclei revealed that a substantial portion of these are burst-generating cells. Application of norepinephrine (NE), the glutamate metabotropic receptor agonist 1S,3R-aminocyclopentane-1,3- dicarboxylic acid (ACPD), or ACh to layer V burst-generating cells resulted in depolarization and a subsequent shift in firing pattern from spontaneously bursting to single-spike activity. Pharmacological analysis of these responses indicated that they are mediated by the alpha 1-adrenoceptor for NE and the muscarinic subtype for ACh. Thus, the NE response was mimicked by the alpha-agonist phenylephrine but not by the beta-agonist isoprenaline, and was completely blocked by the alpha 1-antagonist prazosin but not by the alpha 2-antagonist yohimbine or the beta-antagonist propranolol. Finally, the ACh effect could be mimicked by the muscarinic agonist acetyl-beta-methylcholine (MCh) and was blocked by the muscarinic antagonist scopolamine. Intracellular recordings revealed that the NE-, MCh-, and ACPD-induced responses in bursting neurons are due to the direct activation of receptors on these cells, since block of synaptic transmission with local application of TTX or bath application of low [Ca2+]o and raised [Mg2+]o did not block the postsynaptic responses. Voltage-clamp analysis of the currents involved in the depolarizing responses of bursting cells revealed that activation of alpha 1-adrenergic, muscarinic, or glutamate metabotropic receptors resulted in a decrease in a potassium conductance that consisted of both a voltage-independent component and a voltage- and Ca(2+)-sensitive component. These results suggest that increased activity in noradrenergic, cholinergic, and glutamatergic pathways may control the firing mode of layer V corticotectal and corticopontine pyramidal cells by determining the resting membrane potential through modulation of both voltage-dependent and voltage-independent K+ conductances.(ABSTRACT TRUNCATED AT 400 WORDS)